The Correlation of Gadget Addiction Level with Sleep Quality to Student in 7 Mataram of Public Primary School in Mataram City and 1 Gunungsari of Public Primary School in West Lombok Regency - Yofani Laurintia; Mahardika, Agustine; Niti Wedayani , Anak Agung Ayu (Jurnal Kedokteran, 2019)
Background: Information and communication technology in the world is growing rapidly. One form of information and communication technology in society today is the gadget. In Indonesia, the use of gadgets has become a trend for students aged less than 15 years old by 27,9%. Trends in the use of gadgets at that age are feared to cause addiction of gadget and have negative impacts on health, one of which causes disturbed sleep quality. The main objective of this study is to determine the correlation of gadget addiction level with sleep quality in students, especially students in 7 Mataram and 1 Gunungsari of public primary school. So that can increase our knowledge about the correlation between gadget addiction level to sleep quality. Method: This study method is analytic observational with cross sectional research design in class 4th and 5th of 7 Mataram and 1 Gunungsari of public primary school that use purposive sampling technique and samples are asked to fill the questionnaire of gadget addiction level (SAS-SV) and sleep quality (PSQI). Result: From 104 respondents, most of the gadget addiction level were low risk category 78 (75.0%) and most of respondent had a good sleep quality 76 (73.1%). Data analysis using gamma correlation test obtained (p) = 0.205 and (r) = 0.293. Conclusion: There is no significant correlation between the level of gadget addiction with sleep quality.